Impact of Meteorological Conditions on Airborne Particulates (PM2.5 & PM10) Concentration on Universiti Tun Hussein Onn Malaysia (UTHM) Ambient - Thomas, Whitney; Mat Daud, Azra Munirah (Recent Trends in Civil Engineering and Built Environment, 2024)
The goal of this study at UTHM is to assess the impact of meteorology conditions on particle concentration in ambient air. Numerous human activities occur in the surroundings of UTHM, which may contribute to air pollution. There are two types of air pollutants: primary and secondary. Sulphur dioxide, nitrogen oxides, and ozone are the most common secondary pollutants in Malaysia. There are now more airborne pollutants monitoring devices available, with varying types, prices, flexibility, and accuracy. This study will employ a Met One E – Sampler and a Meteo Compact Station to monitor particle concentrations in Malaysia's Universiti Tun Hussein Onn (UTHM). The data was collected over 14 days at two monitoring stations: FKAAB and Makmal Kejuruteraan Bahan Termaju (FKAAB). Particulate matter concentration, wind speed, relative humidity, and temperature are to be analyzed. The Department of Environment (DOE) has established the New Ambient Air Quality Standard (NAAQS), which establishes the concentration limits of each pollutant to monitor the air quality status. Airborne particle pollutants are dangerous because they are invisible but have major effects on individuals and the environment. This research will improve the air quality in UTHM, preventing health issues and significant inconveniences to the surrounding area.